ANALISIS DAYA SAING EKONOMI KABUPATEN SIMALUNGUN SUMATERA UTARA - Ricky Jaya Dinata; Paidi Hidayat (Ekonomi dan Keuangan, 2015)
This study aimed to analyze the factors that affect and be decisive economic competitiveness Simalungun in 2015 by using the method of Analytical Hierarchy Process (AHP). By using purposive sampling method, this study uses primary data with questionnaires and interviews with 30 respondents consisting of students, teachers, civils, bureaucracy, banking, non-banking, and entrepreneurs.Results from this research that the infrastructure factor becomes the most important factor in improving economic competitiveness Simalungun regency with a weight of 0,392, followed by the regional economy factors (0,221), then a factor of labor and productivity (0,199), socio political factor (0,098), and the final is institutional factors (0,090).Keywords: Economic Competitiveness, Analytical Hierarchy Process (AHP)